Evaluation of the performance of a compartment reactor for the disposal of heavy metals (International Seven Journal of Multidisciplinary, 2023)
Inadequate final disposal of liquid waste, especially industrial process effluents and domestic sewage, has caused serious environmental problems, especially in large cities. About 70,000 chemical compounds are available on the market and 500 to 1,000 compounds are produced annually, which are somehow disposed of as domestic or industrial effluents and are responsible for contamination of water bodies. In the face of the environmental catastrophe that is present in order to guarantee the preservation of humanity's way of life, sewage treatment systems, especially the so-called alternative ones, present themselves as a beneficial and important source for study and development in research centers outside and within the world. Brazil. Such emphasis on alternative systems is due to the low relative cost of deployment and greater ease of handling and maintenance. Alternative treatment systems in constant study include anaerobic reactors. Anaerobic reactors are an important sanitary tool to use because they require short hydraulic detention time and useful area for implantation. They are compartments that promote the treatment from the biochemical reactions present by the bacteria contained in the sewage. This research included monitoring the removal of existing heavy metals in a pilot system deployed at UNICAMP from to January 2023. The system evaluated the inlet and outlet concentrations of the system and relied on the synchrotron radiation detection technique. of metals and other chemical elements. For the five week study period, the initial results showed a percentage efficiency for the compounds of: phosphorus (50.05%); sulfur (already commented); chlorine (51.12%); potassium (51.15%) and zinc (52.63%). This showing the great positive impact of the anaerobic reactor system.